2014
DOI: 10.1063/1.4876722
|View full text |Cite
|
Sign up to set email alerts
|

Highly deformable actuators made of dielectric elastomers clamped by rigid rings

Abstract: In the nascent field of soft machines, soft materials are used to create devices that actuate robots, sense environment, monitor health, and harvest energy. The soft materials undergo large deformation in response to external stimuli, often leading to instability that is usually undesirable but sometimes useful. Here we study a dielectric elastomer membrane sandwiched between two soft conductors, rolled into a hollow tube, pre-stretched in the hoop direction, and fixed at the ends of the tube to two rigid ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Teh et al [9] developed a cylindrical actuator, which significantly enlarged the electrically induced linear strains to 200%. Lu et al [10] conducted the theoretical analysis of cylindrical actuator and found out how the height-to-radius ratio of the tube and loading conditions affected the actuation. There also existed some cone-like (loudspeaker-type) linear DE actuators [11][12][13] which could generate a large deformation out of the membrane plane when actuating and stay in the plane without actuating.…”
Section: Dielectric Elastomer Linear Actuatorsmentioning
confidence: 99%
“…Teh et al [9] developed a cylindrical actuator, which significantly enlarged the electrically induced linear strains to 200%. Lu et al [10] conducted the theoretical analysis of cylindrical actuator and found out how the height-to-radius ratio of the tube and loading conditions affected the actuation. There also existed some cone-like (loudspeaker-type) linear DE actuators [11][12][13] which could generate a large deformation out of the membrane plane when actuating and stay in the plane without actuating.…”
Section: Dielectric Elastomer Linear Actuatorsmentioning
confidence: 99%
“…To prevent failure and to harness the large deformation of dielectric elastomers, it is necessary to construct a theoretical framework. Based on parameter analysis and loading design, many sensors (Jung et al, 2008;Son and Goulbourne, 2009;Gisby et al, 2013;Liu J.J. et al, 2015), actuators (Carpi and Rossi, 2004;Carpi et al, 2005;2007;Aschwanden and Stemmer, 2006;Plante and Dubowsky, 2007;Shankar et al, 2007;Wissler and Mazza, 2007;Biddiss and Chau, 2008;Moscardo et al, 2008;Kovacs et al, 2009;Liu et al, 2009b;Carpi et al, 2010;Fang et al, 2010;Akbari and Shea, 2012;Son et al, 2012;Giousouf and Kovacs, 2013;Haus et al, 2013;La and Lau, 2013;Shian et al, 2013;Hunt et al, 2014;Lu et al, 2014;Nguyen C.H. et al, 2014;Nguyen C.H.…”
Section: Hyperelastic Model Of a Dielectric Elastomermentioning
confidence: 99%
“…Many DE configurations were proposed and studied. Some examples include equal-biaxial configuration [5], flat-clamped configuration [6], stacked configuration [7], tubular configuration [8], loudspeaker configuration [9] and parallelogram configuration [10].…”
Section: Introductionmentioning
confidence: 99%